Observational characterization of Central Javanese local ducks across agroecological zones and rearing systems - SUPRANOTO SUPRANOTO; ELLY TUGIYANTI; NOVIE ANDRI SETIANTO (Society for Indonesian Biodiversity, 2026)
Abstract. Supranoto, Tugiyanti E, Setianto NA. 2026. Observational characterization of Central Javanese local ducks across agroecological zones and rearing systems. Biodiversitas 27 (6): d270607. https://doi.org/10.13057/biodiv/d270607. Local duck farming in Central Java spans heterogeneous agroecological zones and management systems, yet field data on phenotype, natural feed, and egg quality are limited. This observational study characterized qualitative and quantitative phenotypic traits, natural-feed (crop-content) composition, and selected egg-quality parameters of local ducks across four altitude-based zones (coastal, lowland, midland, highland) and three rearing systems (extensive grazing, intensive colony, intensive battery). Qualitative traits were scored in 300 ducks, morphometrics in 90 ducks, crop contents in 12 ducks (three per zone), and egg quality in two one-way ANOVA subsets. Brown and light-brown plumage predominated, whereas beak and shank pigmentation were consistent. Body length, neck length, and shank length were significantly larger under battery rearing (p<0.01), whereas body weight and five other traits did not differ. Because breed and farm were not modeled, these differences reflect combined genetic and management associations. On an as-fed basis, natural feed in all zones fell below commercial protein and energy specifications. Egg weight, yolk color, yolk pH, and albumen pH differed among zones, partly reflecting duck type; among systems, only albumen pH differed. These baseline findings require replicated genetic, nutritional, and production studies before management recommendations are generalized.